Economic burden of primary compared with recurrent Clostridium difficile infection in hospitalized patients: a prospective cohort study. Issue 3 (July 2016) - Shah, D.N.; Aitken, S.L.; Barragan, L.F.; Bozorgui, S.; Goddu, S.; Navarro, M.E.; Xie, Y.; DuPont, H.L.; Garey, K.W.
Summary: Background: Few studies have investigated the additional healthcare costs of recurrent C. difficile infection (CDI). Aim: To quantify inpatient treatment costs for CDI and length of stay among hospitalized patients with primary CDI only, compared with CDI patients who experienced recurrent CDI. Methods: This was a prospective, observational cohort study of hospitalized adult patients with primary CDI followed for three months to assess for recurrent CDI episodes. Total and CDI-attributable hospital length of stay (LOS) and hospitalization costs were compared among patients who did or did not experience at least one recurrent CDI episode. Findings: In all, 540 hospitalized patients aged 62 ± 17 years (42% males) with primary CDI were enrolled, of whom 95 patients (18%) experienced 101 recurrent CDI episodes. CDI-attributable median (interquartile range) LOS and costs (in US$) increased from 7 (4–13) days and $13, 168 (7, 525–24, 456) for patients with primary CDI only versus 15 (8–25) days and $28, 218 (15, 050–47, 030) for patients with recurrent CDI ( P  < 0.0001, each). Total hospital median LOS and costs increased from 11 (6–22) days and $20, 693 (11, 287–41, 386) for patients with primary CDI only versus 24 (11–48) days and $45, 148 (20, 693–82, 772) for patients with recurrent CDI ( P  < 0.0001, each). The median cost of pharmacological treatment while hospitalized was $60 (23–200) for patients with primary CDI only ( N  = 445) and $140 (30–260) for patients with recurrent CDI ( P  = 0.0013). Conclusion: This study demonstrated that patients with CDI experience a significant healthcare economic burden attributed to CDI. Economic costs and healthcare burden increased significantly for patients with recurrent CDI.